Validation of categories of the International Classification of Functioning, Disability and Health for the elderly - Santos, Silvana Sidney Costa; Ilha, Silomar; Barlem, Edison Luiz Devos; Gautério-Abreu, Daiane Porto; Silva, Bárbara Tarouco da; Alves, Inaiá Santos (Rev Rene, 2016)
Objective: to validate categories of the International Classification of Functioning, Disability and Health directed to the elderly. Methods: methodological study of 13 Brazilian gerontologist nurses. We used an electronic form based on the International Classification of Functioning, Disability and Health, composed of 107 items (45 related to Body functions, 38 to Participation and Activity; 24 to Environment). The form was forwarded by email. The items were evaluated on a Likert scale of five points ranging from 0 to 1.0. Questions with 80.0% and more than 80.0% of appearance. Results: participants validated 21 categories related to Body Functions; 18 categories related to Participation and Activity; three categories related to Environmental Factors. Conclusion: biomedical training in nursing may have directed the preferential validation of categories related to the body and less preference to context/environment.